2013
DOI: 10.2515/therapie/2013045
|View full text |Cite
|
Sign up to set email alerts
|

Medico-economic Evaluation of Health Products in the Context of the Social Security Financing Act for 2012

Abstract: -The participants in round table 6 of the Giens Workshops 2012 drafted recommendations based on the collective interpretation of important elements of the decree concerning the medico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, the lack of these adjustments can be considered to favor dabigatran and rivaroxaban and, thus, is unlikely to alter treatments that currently are on the efficiency frontier. The open-label design of the RELY trial may over-estimate the effect of dabigatran 19,39,40 . In addition, although the ROCKET-AF trial included higher-risk patients compared to those who participated in the RELY and ARISTOTLE trials, an indirect treatment comparison that looked at a sub-group of patients with CHADS 2 !3 revealed that, in relation to apixaban, the degree of risk reduction in the primary efficacy outcome of stroke or SE provided by rivaroxaban was not as great as when all trial patients were included in the analysis 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of these adjustments can be considered to favor dabigatran and rivaroxaban and, thus, is unlikely to alter treatments that currently are on the efficiency frontier. The open-label design of the RELY trial may over-estimate the effect of dabigatran 19,39,40 . In addition, although the ROCKET-AF trial included higher-risk patients compared to those who participated in the RELY and ARISTOTLE trials, an indirect treatment comparison that looked at a sub-group of patients with CHADS 2 !3 revealed that, in relation to apixaban, the degree of risk reduction in the primary efficacy outcome of stroke or SE provided by rivaroxaban was not as great as when all trial patients were included in the analysis 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…In France, a decree concerning the medico-economic evaluation of health products was published in 2012, with an implementation in 2013. The medico-economic evaluation becomes an additional determinant for fixing the prices of health products by the Health Products Economic Committee (Comité économique des produits de santé, CEPS) and, thus, modifies the market access conditions 19 . The objective of this study was, therefore, to conduct an economic evaluation of the currently prescribed treatments for stroke prevention in patients with AF including warfarin, aspirin, and, per the recent guidelines 15 , apixaban, rivaroxaban, and dabigatran from the perspective of the French National Authority for Health (Haute Autorité de Santé, HAS).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing demand for defining reference values for qualifying cost-effectiveness of new products coming to price negotiation in France. Although the issue was first raised in 2012, 12 no such proposal has yet been made. The HAS has conducted a comprehensive literature review exploring methods to measure WTP for a health gain and studies performed to estimate WTP.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other countries where a cost-effectiveness threshold exists, such as England and Wales, 5 Ireland, 8 Netherlands, 9 Slovakia, 10 and Slovenia, 11 it was originally decided in France that such a threshold was irrelevant in a market access process where the reimbursement decision is not based on an incremental cost-effectiveness ratio (ICER). 12 In France, access to reimbursement is determined solely by the medical service (Service Médical Rendu), which takes into account the efficacy and safety of the treatment, its expected use relative to existing treatment strategies, the severity of the condition to be treated, the treatment goal (symptomatic, disease-modifying, or prophylactic), and its anticipated public health interest. For this reason, appraisal of efficiency is taken into account only for price setting.…”
Section: Introductionmentioning
confidence: 99%